Impact of hepatitis C virus heterogeneity on interferon sensitivity: An overview - El-Shamy, Ahmed (Baishideng Publishing Group Inc, 2014)
Hepatitis C virus (HCV) is a major cause of liver disease worldwide. HCV is able to evade host defense mechanisms, including both innate and acquired immune responses, to establish persistent infection, which results in a broad spectrum of pathogenicity, such as lipid and glucose metabolism disorders and hepatocellular carcinoma development. The HCV genome is characterized by a high degree of genetic diversity, which can be associated with viral sensitivity or resistance (reflected by different virological responses) to interferon (IFN)-based therapy. In this regard, it is of importance to note that polymorphisms in certain HCV genomic regions have shown a close correlation with treatment outcome. In particular, among the HCV proteins, the core and nonstructural proteins (NS) 5A have been extensively studied for their correlation with responses to IFN-based treatment. This review aims to cover updated information on the impact of major HCV genetic factors, including HCV genotype, mutations in amino acids 70 and 91 of the core protein and sequence heterogeneity in the IFN sensitivity-determining region and IFN/ribavirin resistance-determining region of NS5A, on virological responses to IFN-based therapy.